1985
DOI: 10.1177/096032718500400206
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of some Industrial Uranium Tetrafluorides after Deposition in the Rat Lung

Abstract: Two commercially produced natural uranium tetrafluorides were administered to rats either by inhalation or direct injection into the lungs. The results: 1 show that, for both materials uranium is cleared rapidly from the lungs, much of it to the blood 2 show that the distribution of uranium amongst body tissues, and the fraction of the systemic content excreted in urine, is similar to that obtained after the administration of U(VI) bicarbonate 3 sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The reported biokinetic behaviour of UF 4 is complex. Measurement of urinary excretion after inhalation by workers (Chalabreysse et al., 1989) and experiments in rats and baboons (Stradling et al., 1985a; André et al., 1989; Ansoborlo et al., 1990) showed that a large fraction (35–40%) of the lung deposit was absorbed to the blood by 7 d after administration. However, considerable variations in behaviour were observed, with some experiments indicating assignment to default Type F and others to default Type M. (844) Zhao and Zhao (1990) reported measurements of urinary excretion of uranium made for 3 y after an accidental inhalation of UF 4 powder by a worker.…”
Section: Uranium (Z = 92)mentioning
confidence: 99%
See 1 more Smart Citation
“…The reported biokinetic behaviour of UF 4 is complex. Measurement of urinary excretion after inhalation by workers (Chalabreysse et al., 1989) and experiments in rats and baboons (Stradling et al., 1985a; André et al., 1989; Ansoborlo et al., 1990) showed that a large fraction (35–40%) of the lung deposit was absorbed to the blood by 7 d after administration. However, considerable variations in behaviour were observed, with some experiments indicating assignment to default Type F and others to default Type M. (844) Zhao and Zhao (1990) reported measurements of urinary excretion of uranium made for 3 y after an accidental inhalation of UF 4 powder by a worker.…”
Section: Uranium (Z = 92)mentioning
confidence: 99%
“…The unusual behaviour may have been caused, in part, by the size of the intake, which was sufficient to give rise to biochemical indications of kidney dysfunction. (845) Hodgson et al. (2000) derived absorption parameter values from the results of a study by Stradling et al. (1985a) in which the biokinetic of uranium in rats were followed for 360 d after inhalation and 168 d after intratracheal administration of two forms of UF 4 : (i) f r = 0.51, s r = 0.10 d −1 , and s s = 0.0074 d −1 ; and (ii) f r = 0.52, s r = 0.11 d −1 , and s s = 0.0039 d −1 .…”
Section: Uranium (Z = 92)mentioning
confidence: 99%
“…These variations relate to the experimental protocol, oxygenation of the solvents, etc. (18,19), or to the physical characteristics of the compounds (3). The in vitro technique, using specialized cells such as alveolar macrophages, markedly reduced the influence of these different parameters because it simulated the long-term in vivo intracellular dissolution ofparticles deposited in alveoli and phagocytized by macrophages (16,17,20).…”
Section: Discussionmentioning
confidence: 99%
“…Table 3.2. Leach et al 1973;Cook and Holt 1974;Pomroy and Noel 1981;Schieferdecker et al 1985;Price 1989;Stradling et al 1989b;Métivier et al 1992;Eidson 1994;Chazel et al 2000b;Ansoborlo et al 2002;Stradling et al 2002 Uranium West et al 1979;Eidson and Mewhinney 1980;Chalabreysse et al 1989;Stradling et al 1989aStradling et al , 2002Eidson 1990Eidson , 1994Métivier et al 1992;Barber and Forrest 1995;Ansoborlo et al 1998bAnsoborlo et al , 2002Chazel et al 1998 Uranium Stradling et al 1985Stradling et al , 2002Chalabreysse et al 1989;André et al 1989;Ansoborlo et al 1990Ansoborlo et al , 2002Eidson 1994;Chazel et al 2000a Uranium Galibin and Parfenov 1971;Cook and Holt 1974;Boback 1975;Eidson and Mewhinney 1980;Damon et al 1984;Stradling et al 1987Stradling et al , 2002Eidson 1994;Ansoborlo et al 2002 In vitro studies indicate dissolution rate varies with mixture of materials and preparation process. Differences found in dissolution rates of low-fired yellowcake (dried at less than 400° C) and high-fired (calcined) yellowcake (dried at 4...…”
Section: Application Of the Hrtm To Various Forms Of Uraniummentioning
confidence: 99%